2020
DOI: 10.22146/ifnp.46921
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I-converting Enzyme (ACE) Inhibitory Activity of Ace Inhibitory Peptides Produced during the Fermentation of Pigeon Pea (Cajanus cajan) Tempe

Abstract: Fermentation products are common sources of angiotensin I-converting enzyme (ACE) inhibitory peptides used for hypertension treatment. This research investigated the effect of fermentation time on the ACE inhibitory activity produced during the fermentation of pigeon pea tempe and aimed to determine the optimal fermentation time to obtain pigeon pea tempe with the highest ACE inhibitory activity. Seeds were inoculated with Raprima® (0.02% w/w) containing Rhizopus oligosporus spores and fermented for 0-96 h. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…However, compared with the finding of Pebrianti et al (2019) on the ACE inhibition of peptide fraction of 48 h-fermented pigeon pea tempe, all of the hydrolyzed pigeon pea tempe peptide fractions in the present study underwent decrement, especially the F3 peptides. This result suggests that the activity of bioactive peptides does not depend on their MW or size.…”
Section: Enzyme Inhibitory Activitycontrasting
confidence: 74%
See 4 more Smart Citations
“…However, compared with the finding of Pebrianti et al (2019) on the ACE inhibition of peptide fraction of 48 h-fermented pigeon pea tempe, all of the hydrolyzed pigeon pea tempe peptide fractions in the present study underwent decrement, especially the F3 peptides. This result suggests that the activity of bioactive peptides does not depend on their MW or size.…”
Section: Enzyme Inhibitory Activitycontrasting
confidence: 74%
“…The R. oligosporus used in tempe making produced protease that hydrolyzed the protein of the pigeon pea during fermentation. Pebrianti et al (2019) found that the inhibitory activity of 48 h-fermented pigeon pea tempe is 76.14%. The inhibitory activity of unhydrolyzed tempe was only slightly lower than that of the hydrolyzed tempe.…”
Section: Angiotensin-i-converting Enzyme Inhibitory Activity Of the Peptidementioning
confidence: 98%
See 3 more Smart Citations